The Context of Demarcation in Nature of Science Teaching: The Case of Astrology - (:unkn) unknown (SPRINGER, 2011)
The aim of developing students' understanding of the nature of science [NOS] has been considered an important aspect of science education. However, the results of previous research indicate that students of various ages and even teachers possess both inaccurate and inappropriate views of the NOS. Such a failure has been explained by the view that perceptions about the NOS are well assimilated into mental structures and resistant to change. Further, the popularization of pseudoscience by the media and the assimilation of pseudoscience into previously established scientific fields have been presented as possible reasons for erroneous popular perceptions of science. Any teaching intervention designed to teach the NOS should first provoke individuals to expose their current ideas in order to provide them the chance to revise or replace these conceptual frameworks. Based on these assumptions, the aim of this study was to determine whether a teaching context based on the issue of demarcation would provide a suitable opportunity for exposing and further developing the NOS understandings of individuals enrolled in a teacher education course. Results indicate that a learning intervention based on the issue of demarcation of science from pseudoscience (in the specific case of astrology) proved an effective instructional strategy, which a majority of teacher candidates claimed to plan to use in their future teachings.
Keywords: TEACHERS CONCEPTIONS; STUDENTS VIEWS; BELIEFS; COURSES; GOALS